Alpha-Toxin Promotes Staphylococcus aureus Mucosal Biofilm Formation - Anderson, Michele J.; Lin, Ying-Chi; Gillman, Aaron N.; Parks, Partick J.; Schlievert, Patrick M.; Peterson, Marnie (Frontiers in Cellular and Infection Microbiology, 2012)
Staphylococcus aureus causes many diseases in humans, ranging from mild skin infections to serious, life-threatening, superantigen-mediated Toxic Shock Syndrome (TSS). S. aureus may be asymptomatically carried in the anterior nares or vagina or on the skin, serving as a reservoir for infection. Pulsed-field gel electrophoresis clonal type USA200 is the most widely disseminated colonizer and the leading cause of TSS. The cytolysin α-toxin (also known as α-hemolysin or Hla) is the major epithelial proinflammatory exotoxin produced by TSS S. aureus USA200 isolates. The current study aims to characterize the differences between TSS USA200 strains [high (hla+) and low (hla−) α-toxin producers] in their ability to disrupt vaginal mucosal tissue and to characterize the subsequent infection. Tissue viability post-infection and biofilm formation of TSS USA200 isolates CDC587 and MN8, which contain the α-toxin pseudogene (hla−), MNPE (hla+), and MNPE isogenic hla knockout (hlaKO), were observed via LIVE/DEAD® staining and confocal microscopy. All TSS strains grew to similar bacterial densities (1–5 × 108 CFU) on the mucosa and were proinflammatory over 3 days. However, MNPE formed biofilms with significant reductions in the mucosal viability whereas neither CDC587 (hla−), MN8 (hla−), nor MNPE hlaKO formed biofilms. The latter strains were also less cytotoxic than wild-type MNPE. The addition of exogenous, purified α-toxin to MNPE hlaKO restored the biofilm phenotype. We speculate that α-toxin affects S. aureus phenotypic growth on vaginal mucosa by promoting tissue disruption and biofilm formation. Further, α-toxin mutants (hla−) are not benign colonizers, but rather form a different type of infection, which we have termed high density pathogenic variants (HDPV).